The Importance of Bone Mineral Density in Hip Arthroplasty: Results of a Survey Asking Orthopaedic Surgeons about Their Opinions and Attitudes Concerning Osteoporosis and Hip Arthroplasty - Gerrit Steffen Maier; Kristina Kolbow; Djordje Lazovic; Uwe Maus (Advances in Orthopedics)
Objective. In patients scheduled to undergo total joint arthroplasty of the hip, the bone quality around the joint affects the safety of prosthetic implantation. Bone strength is clinically assessed by measuring bone mineral density (BMD); therefore we asked if BMD is important to orthopaedic surgeons performing hip arthroplasty. Methods. In a 14-question survey, we asked about treatment patterns with respect to BMD, osteoporosis work-up, and treatment for patients with low BMD scheduled to undergo hip arthroplasty. Results. 72% of all asked orthopaedics reported to use cementless implants as a standard in hip arthroplasty. Over 60% reported that low BMD is a reason to reconsider operation strategies, but only 4% performed BMD measurement preoperatively. 26% would change their treatment strategy in case of a BMD (T-Score) between −1.5 and −2 and 40% in case of a T-score between −2 and −2.5, and 29% would change their intraoperative strategy if a T-score smaller than −2.5 was measured. Conclusion. The majority of orthopaedic surgeons who responded to the survey reported that they do not perform routine measurement of BMD before arthroplasty. However, most surgeons commented that low bone mineral density will influence their surgical plan and the implant design.